7 - Leadership Challenges of Middle-level Academics in Universities in Nigeria - Afolabi, Olugbemiga Samuel (Journal of Higher Education in Africa, 2022)
One key issue confronting universities in Nigeria is the leadership challenges facing middle-level academics, especially at the Senior Lecturer cadre. This problem is rooted in a lack of leadership preparation and training for this category of academics. Through primary data sourced from interviews and secondary data, this paper analyses the underlying challenges middle-level academics face that inhibit their effective performance in leadership posts to which they have been appointed. The analysis is with a view to understanding and proffering possible solutions to the leadership challenges of middle-level academics in universities in Nigeria.